Integrated demand-driven supply chain model design for fresh fruits and vegetables - Tort, Ömer Özgür (My University, 2022)
Bu kapsamında; yaş meyve sebze tedarik zinciri boyunca meydana gelen sorunlar tespit edilmiş ve iki çözüm yaklaşımı geliştirilmiştir. İlk olarak, bir talep tahmin modeli yapılandırılmıştır. Migros Ticaret A.Ş.'nin satış noktası verilerinden, TÜİK'ten toplanan verilerden ve Ticaret Bakanlığı'ndan alınan verilerden yararlanılmıştır. Bu analizlerde, modelin prototipi için kuru soğan ve patlıcan seçilmiştir. İstatistiksel analizler, hane tüketiminin tahmin edilebileceğini ve böylece üretimin yaş meyve ve sebze için kolaylıkla planlanabileceğini göstermiştir. İkinci olarak, taze meyve ve sebzeler için finansal ve veri akış modeli önerilmiştir. Bu tezin özgün çıktısı olan bu modele Üretici Finansman Modeli adı verilmiştir. Bu modelin pilot uygulaması da yapılmıştır. Bu pilot uygulama kapsamında, Migros Ticaret A.Ş. ve Ziraat Bankası ortak bir çalışma sergilemiştir. Daha sonra çiftçiler bu modele dahil olmaya başlamıştır. Bu tez, talep tahmin modeli ve Üretici Finansmanı Modeli ile Türkiye'de yaş meyve sebze yüksek enflasyon oranlarının düşürülebileceğini belirtmektedir. Bu tez, (1) talebi tahmin etmenin mümkün olduğunu, (2) finansal ve veri akışı modelinin test edildiğini ve çalıştığının görüldüğünü açıkça göstermektedir. Bu nedenle yaş meyve ve sebzelerde yaşanan sorunlar bu çözüm yaklaşımlarıyla ele alınabilir. Son olarak, tarım sektöründeki engellere uzun vadeli çözüm olarak bir kooperatif altyapısı önerilmiştir. Perakendeci ve çiftçi arasında güvene dayalı bir ilişki kurmak için kooperatiflerin kurulması şiddetle tavsiye edilmektedir.

Within the scope of this doctoral thesis, the problems occurring along the fresh fruits and vegetables supply chain are detected and two solution approaches are developed. First off, a demand forecasting model is structured. The point-of-sales data of Migros Ticaret A.Ş., the data gathered from Turkish Statistical Institute (TUIK) and the data retrieved from The Ministry of Commerce are benefitted from. For these analyses, dry onion and eggplant are chosen to prototype the model. The statistical analyses have shown that the household consumption can be predicted, thus, the production can easily be planned for the fresh fruits and vegetables. Secondly, the financial and data flow model for fresh fruits and vegetables is proposed. This model named as Producer Financing Model which is the novel output of this thesis. The pilot application of this model is implemented too. For this reason, a partnership is established between Migros Ticaret A.Ş. and Ziraat Bank. After, the farmers are started to be involved in this model. This thesis states that the high inflation rates for fresh fruits and vegetables in Turkiye can be reduced with the help of the demand forecast model and the Producer Financing Model. This thesis clearly indicates that (1) it is possible to forecast the demand, (2) the financial and data flow model is tested and seen that it works. Therefore, the problems in the fresh fruits and vegetables can be tackled with these solution approaches. Last but not least, a cooperative infrastructure is proposed to be the long-term solution for the obstacles in the agriculture sector. It is highly recommended to build cooperatives to construct trust-based relationship between a retailer and a farmer.
Taze meyve sebzeler için talebe dayalı bütünleşik tedarik zinciri modeli tasarımı
Keywords: AGRICULTURE; COOPERATIVES; Değer zinciri; DEĞER ZİNCİRİ; DEMAND FORECAST; Engineering; FINANCIAL MODEL; FİNANSAL MODEL; FRUITS; KOOPERATİF; MEYVE; Mühendislik; SEBZE; SUSTAINABILITY; SÜRDÜRÜLEBİLİRLİK VALUE CHAIN; TALEP TAHMİN; TARIM; Value chain; VEGETABLES